2021
DOI: 10.3390/biom11121785
|View full text |Cite
|
Sign up to set email alerts
|

Identification, Synthesis, Conformation and Activity of an Insulin-like Peptide from a Sea Anemone

Abstract: The role of insulin and insulin-like peptides (ILPs) in vertebrate animals is well studied. Numerous ILPs are also found in invertebrates, although there is uncertainty as to the function and role of many of these peptides. We have identified transcripts with similarity to the insulin family in the tentacle transcriptomes of the sea anemone Oulactis sp. (Actiniaria: Actiniidae). The translated transcripts showed that these insulin-like peptides have highly conserved A- and B-chains among individuals of this sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 68 publications
0
14
0
Order By: Relevance
“…(Mitchell et al, 2020). The representative ILP-IlO1-i1did not bind to the insulin orinsulin-like growth factor receptors, but showed weak activity against K V 1.2, 1.3, 3.1, and 11.1 (hERG) channels, as well as Na V 1.4 channels (Mitchell et al, 2021). In addition, two fish- hunting cone snails, Conus tulipa and Conus geographus, have special insulins that are major constituents of their venoms (Safavi-Hemami et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…(Mitchell et al, 2020). The representative ILP-IlO1-i1did not bind to the insulin orinsulin-like growth factor receptors, but showed weak activity against K V 1.2, 1.3, 3.1, and 11.1 (hERG) channels, as well as Na V 1.4 channels (Mitchell et al, 2021). In addition, two fish- hunting cone snails, Conus tulipa and Conus geographus, have special insulins that are major constituents of their venoms (Safavi-Hemami et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The absence of transcripts for any given species may reflect the quality of the specific tissue assayed, transcriptome quality, sequencing depth, or the technology used for sequencing. Cnidoinsulins likely have tissue-specific expression [ 45 ], so transcriptomes without any cnidoinsulins may be from tissue that does not natively express insulin-like venoms. Non-expression also might reflect biological factors, such as lack of transcriptomic activity for a specific gene at the instance of sampling or population-level loss of venom [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…The transcriptome of Sea anemones contain transcripts that closely resemble the well-known venomous peptide conoinsulin from cone snails [ 45 , 46 ]. In a study that examined these peptides in the undescribed actinioidean Sea anemone , Oulactis sp., Mitchell and colleagues showed that the anemone-derived peptides showed signs of binding to both Kv1-3 binding sites and insulin growth receptors [ 45 ]. Similar sequences also occur in the genome of Nematostella vectensis [ 47 ].…”
Section: Introductionmentioning
confidence: 99%
“…as a new source. 600 A peptide, synthesised based upon the tentacle transcriptome, did not bind to insulin or insulin-like growth factor receptors but did show weak activity towards voltage-gated potassium and sodium channels. A systematic search of published genomes and transcriptomes of cnidarians for homologues of the blue protein rpulFKz1, originally described from the jellyfish Rhizostoma pulmo , has identified a family of pigment precursors called the rhizostomins specifically associated with jellyfish in the order Rhizostomeae.…”
Section: Cnidariansmentioning
confidence: 99%